ANALISIS PROBLEMATIKA PENGGUNAAN MODEL BLENDED LEARNING PADA MATERI BANGUN RUANG SISWA KELAS 1 SEKOLAH DASAR - Alfiah Dian Pratiwi; Retno Winarni; Endang Wahyuningrum (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2023)
The use of blended learning models is very necessary in the implementation of educational activities in the era of the Covid-19 pandemic that has hit Indonesia. This research contains an explanation of the problem analysis that accompanies learning with a blended learning model. The purpose of this study is to explain various kinds of problems and problems that occur when the learning process is carried out with a blended learning model in the material for building rooms for grade 1 elementary school students. The method used in this study is descriptive qualitative with an approach to analyzing the situation of conditions in accordance with the facts in the field as the object of study and the object of research. The results of this study are that there are various probelamtics that accompany learning with a blended learning model such as insufficient student independence, parents who have to accompany their students to study, economic limitations to buy internet credit, unstable signals during online learning, the implementation of strict health protocols during study visits, and the concerns of parents who do not want their children to interact directly with teachers and other students in groups because fear of exposure to the coronavirus considering they are still in the 1st grade of elementary school.